Reproductive and lifestyle factors associated with early menopause in Mexican women Factores reproductivos y de estilos de vida asociados con menopausia temprana en mujeres mexicanas - Paola A. Ortega-Ceballos; Carlos Morán; Julia Blanco-Muñoz; Elsa Yunes-Díaz; Maura S. Castañeda-Iñiguez; Jorge Salmerón (Instituto Nacional de Salud Pública, 2006)
OBJECTIVE: The purpose of this study was to evaluate the relationship between certain reproductive and lifestyle factors and the occurrence of early natural menopause. MATERIAL AND METHODS: A case/control study was conducted on a basal population of 2 510 women participating in the "Mexican Institute of Social Security health workers cohort study". Cases were defined as those women for whom natural menopause presented by age 47. Information was obtained through a self-administered questionnaire. RESULTS: The risk of early menopause is associated with short menstrual cycles [< 26 days, OR=3.79 (IC 95%1.37-10.52)], a short period of oral contraceptives use [<1 year, OR=2.63 (IC 95% 1.10-6.29)], a lower number of pregnancies [<2, OR=1.63 (IC 95% 1.03-2.57)], low body mass index [< 27 kg/m², OR=1.64 (IC 95% 1.10-2.43)], low schooling level [<6 years, OR=3.02 (IC 95% 1.26-7.23)], smoking history [>15 cigarettes/day, OR=2.7 (IC 95% 1.00-7.30)], and birth cohorts [>1950, OR=4.09 (IC 95% 2.62-6.39)]. COCLUSIONS: The findings of this study suggest that both reproductive and lifestyle factors are significant elements in the occurrence of early menopause in Mexican women. OBJETIVO : Evaluar la relación entre factores reproductivos, estilo de vida y la ocurrencia de menopausia natural temprana. MATERIAL Y MÉTODOS : Un estudio de casos y controles fue conducido en una población basal de 2 510 mujeres participantes en la "Cohorte de trabajadores IMSS". Los casos fueron definidos como aquellas mujeres que presentaron la menopausia natural a los 47 años o menos. La información fue colectada a través de cuestionarios autoapicables. RESULTADOS: El riesgo de menopausia temprana está asociado con ciclos menstruales cortos [<26 días, RM=3.79 (IC 95%1.37-10.52)], poco tiempo de uso de anticonceptivos orales [<1 año, RM=2.63 (IC 95% 1.10-6.29)], bajo número de embarazos [<2, RM=1.63 (IC 95% 1.03-2.57)], índice de masa corporal bajo [< 27 kg/m², RM=1.64 (IC 95% 1.10-2.43)], baja escolaridad [<6 años, RM=3.02 (IC 95% 1.26-7.23)], tabaquismo [>15 cigarros/día, RM=2.7 (IC 95% 1.00-7.30)], y cohorte de nacimiento [>1950, RM=4.09 (IC 95% 2.62-6.39)]. CONCLUSIONES: Los hallazgos sugieren que tanto factores reproductivos como de estilo de vida son elementos significantes en la ocurrencia de la menopausia a edad temprana en mujeres mexicanas.